Annona squamosa: Basic understanding and recent updates in therapeutics - JAYENDRA (International Journal of Pharma and Bio Sciences, 2018)
Annona Squamosa, a widely used Indian medicinal plant family: Annonaceae is reported to have a very excellent antidiabetic activity & other high medicinal value. In last two decades, Annona squamosa has witnessed a lot of pharmacological studies. The plant consists of a variety of potent molecules like Annonins, linear acetogenins, cyclopeptides, hydroxylated bistetrahydrofurans, & other alkaloids. It has been found to have antilipidimic, insecticide, antiovulatory, abortifacient, antioxidative, Antidiabetic & antirheumatic activities. Now many parts of the plant have been screened for variety of pharmacological activity. A lot of scientific evidence is now available to prove the efficacy of this plant & further investigations are needed to get maximum benefit out of this valuable medicinal plant. The objective of present study is to systematically review the data published in last ten years and help the researchers who are planning to work on the plant Annona squamosa targeting antidiabetic activity. The outcome of this work would be a manuscript which consists of important chemical compounds reported so far from Annona squamosa. The compounds reported in the present study relate to antidiabetic activity and cholesterol management.